2012
DOI: 10.1007/s11033-012-2270-z
|View full text |Cite
|
Sign up to set email alerts
|

Association of methylenetetrahydrofolate reductase gene 677C > T polymorphism and Down syndrome

Abstract: The association between Down syndrome (DS) and maternal polymorphisms in genes encoding folic acid metabolizing enzymes remains a controversial issue. A meta-analysis was performed to evaluate the association of maternal MTHFR 677C > T polymorphism and the risk of having a child with DS. Case-control studies were screened from major literature databases. Twenty articles from 13 countries worldwide, with a total of 2,101 DS and 2,702 control mothers, attended the inclusion criteria. We found a 50 % increase for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 54 publications
3
22
0
Order By: Relevance
“…Dietary regimens rich in folate, such as the Mediterranean diet, could mask the effect of certain polymorphisms, as it happens for the MTHFR 677C>T one, the most studied polymorphism of the folate pathway, which is associated with increased risk of sporadic AD in Asians but not in Caucasians [16]. It was also suggested that geographic factors, such as the latitude, could interfere with ultraviolet B solar radiation and promote, in less pigmented skins, intravascular folate photolysis, thereby affecting circulating folate levels and folate metabolism [29]. In this regard, a recent literature meta-analysis reported a significant effect of the MTHFR 677C>T polymorphism on pregnancy outcome only in subtropical regions [29], and it is also of interest that the RFC-1 80G>A polymorphism was associated with increased chromosome damage in blood cells of healthy Australian individuals but not in those of healthy Italian ones [30, 31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary regimens rich in folate, such as the Mediterranean diet, could mask the effect of certain polymorphisms, as it happens for the MTHFR 677C>T one, the most studied polymorphism of the folate pathway, which is associated with increased risk of sporadic AD in Asians but not in Caucasians [16]. It was also suggested that geographic factors, such as the latitude, could interfere with ultraviolet B solar radiation and promote, in less pigmented skins, intravascular folate photolysis, thereby affecting circulating folate levels and folate metabolism [29]. In this regard, a recent literature meta-analysis reported a significant effect of the MTHFR 677C>T polymorphism on pregnancy outcome only in subtropical regions [29], and it is also of interest that the RFC-1 80G>A polymorphism was associated with increased chromosome damage in blood cells of healthy Australian individuals but not in those of healthy Italian ones [30, 31].…”
Section: Discussionmentioning
confidence: 99%
“…It was also suggested that geographic factors, such as the latitude, could interfere with ultraviolet B solar radiation and promote, in less pigmented skins, intravascular folate photolysis, thereby affecting circulating folate levels and folate metabolism [29]. In this regard, a recent literature meta-analysis reported a significant effect of the MTHFR 677C>T polymorphism on pregnancy outcome only in subtropical regions [29], and it is also of interest that the RFC-1 80G>A polymorphism was associated with increased chromosome damage in blood cells of healthy Australian individuals but not in those of healthy Italian ones [30, 31]. Moreover, the presence/absence of other polymorphisms of the pathway could mask or potentiate the effect of a single one [26].…”
Section: Discussionmentioning
confidence: 99%
“…DS (down syndrome) also known as trisomy 21 is a chromosomal disease that is associated with growth and mental retardation [50,51]. DS results from an over-expression of three extra copies of the gene on chromosome 21 causing failure of normal chromosomal separation during meiosis [21,51,52].…”
Section: Down Syndromementioning
confidence: 99%
“…DS results from an over-expression of three extra copies of the gene on chromosome 21 causing failure of normal chromosomal separation during meiosis [21,51,52]. DS affects approximately 1 in 1000 to 1100 live births worldwide and 1 out of every 700 newborns in the US [53,54].…”
Section: Down Syndromementioning
confidence: 99%
See 1 more Smart Citation